S21-4: What Have We Learned From 15 Years of Designing and Evaluating Healthcare Professional Training Programmes for Physical Activity Promotion Randomised Controlled Trials? (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Over the last 15 years, we have trained healthcare professionals (HCPs) to deliver interventions that support clinical populations to change their physical activity behaviour. We will share our learning and summarise the key components to include in designing or evaluating healthcare professional training programmes for physical activity promotion in clinical populations.Methods: Our studies were feasibility, pilot, or definitive randomised controlled trials. Some were designed to investigate the impact of HCP training on their communication style as the primary outcome, whereas others had clinical endpoints, physical activity or feasibility outcomes. All delivered an evidence-based bespoke training programme to HCPs using mixed methods including lectures, group discussion, self-reflection, video examples, goal setting, role play, micro-teaching, peer and facilitator feedback. The impact of training was determined by a mix of HCP satisfaction, learning during training [confidence, knowledge, and skills] and behaviour [audio-recorded delivery and independent rating of the trained skills within randomised controlled trial settings], as well as qualitative feedback from HCP and patients.Results: We primarily trained physiotherapists to deliver interventions within publicly funded healthcare systems in Ireland, United Kingdom, and Canada. The theoretical underpinning of our training programmes and interventions strengthened over time as our experience developed and behaviour change models were published. Interventions were delivered to healthcare seeking people with physical (musculoskeletal and respiratory) and mental health conditions. Self-Determination Theory (SDT) and the 5As model were common, but not the sole, communication skills training frameworks used. There was some consistency in behaviour change techniques used, depending on the number of behavioural targets. In one definitive trial independent ratings demonstrated that physiotherapists (n = 12) who completed an SDT-based communication skills training programme were significantly more supportive than controls (n = 12) during a one-to-one treatment session (d = 2.27; 95% confidence interval = 1.18–3.21; p < 0.001). Comparable effects were found within a feasibility trial process evaluation of a group-based intervention, where physiotherapists were also satisfied with the training methods, and their confidence, knowledge, and competence significantly improved following training. Interventions led to within group changes in physical activity outcomes, with inconsistent evidence for between group differences.Conclusions: With each successive trial we have refined our approach to HCP training, identified key learning on how best to train HCPs to deliver tailored physical activity promotion programmes in low-active clinical populations, and how to measure their impact.Support/Funding Source: Charitable Trust, Northern Ireland (NI) Chest Heart and Stroke; Department of Employment and Learning, NI; Physiotherapy Research Foundation (PRF/08/1), Chartered Society of Physiotherapy, London, United Kingdom; Saskatchewan Health Research Foundation, Canada; Health Research Board, Ireland.Keywords: Education, health behaviours, lifestyle medicine, students